Improving the freshness of pale lager beers - Maia, Carolina (2023)
Sensory ageing of beer is nowadays one of the major problems of the brewing industry. Myriad factors impact on the beer ageing profile, from the quality of the raw materials and brewing process to the storage conditions of the finished product. The research reported in this thesis aimed to better understand the relative contribution of raw materials to beer flavour stability with a focus on the use of unmalted adjuncts such as corn and rice. Further objectives were to compare the predictive value of commonly applied analytical measures of flavour stability and thus to identify early indicators of staling potential upstream in wort production. Firstly, a study of flavour stability metrics in a range of six commercial beers was undertaken (Chapter 3) to establish key methodologies for the thesis and test some initial hypotheses. For example, interesting discrepancies were observed between the displacement of staling aldehydes from the beers during forced ageing experiments, and the release of aldehydes following addition of a competitive binding agent (4-VP), which has been proposed to predict staling potential of fresh beers. Our study suggested that 4-VP has varying efficacy at displacing the major beer staling aldehydes. From early stages of beer production to finished beer the impacts of adjunct usage and incorporation rate on beer flavour stability metrics were investigated. A significant improvement in flavour stability metrics was observed among wort samples (Chapters 4, 5 and 6) as the corn or rice adjunct rate increased. Significant improvements in flavour stability metrics were identified at ≥ 19% corn for Thiobarbituric acid index (TBI), staling aldehydes and transition metal ions (p<0.05). Oxidative stability also significantly improved (p<0.05) in wort samples at 19-40% corn (in comparison to all-malt) when using a standardized brewing recipe with application of exogenous proteases for the high adjunct brews. Despite the beneficial effects of corn usage observed in wort samples, these were not fully translated to fresh finished beer (e.g. with regard to staling aldehyde levels or transition metal ion concentrations). As the beers were aged, significant differences started to appear in the levels of staling volatiles as the corn incorporation rate varied (Chapter 6). Analytical measurements showed a significant negative linear correlation (p<0.05) with corn rate for dimethylsulfide, 2-methylpropanal, phenylethanal and furfural after natural ageing for 39 weeks. Thus, corn incorporation either reduced the number of precursors for de novo formation or reduced the bound-state potential as the beer aged. Sensory data revealed a significant reduction (p<0.05) in the perception of staling compounds (i.e. musty, cardboard, metallic and fruity/sweet flavours) at 19-30% of corn in comparison to the all-malt aged beer. However, the 40% adjunct aged beer had similar staling flavour scores as the all-malt beer, which might have been related to the use of mash proteases at higher adjunct levels, and requires further investigation. Chapter 7 focused on the stability of corn adjunct during storage prior to brewing. Globally, corn grits samples vary in factors such as particle size range, lipid and metal ion contents. The impacts of these on the sample shelf-life and development of oxidation markers was studied. Partial least squares regression analysis showed that the most important factors in the formation of trihydroxy fatty acids during storage were surface area, time and temperature of storage (R2cv=0.79). Thus, the best strategy to extend shelf-life is to store the grains, ideally in kernels, and at lower temperature. Lastly, Chapter 8 reports fundamental studies designed to improve understanding of how key staling compounds interact with the beer matrix (i.e. other soluble components). This is important in terms of the carry-over of bound forms of staling aldehydes from upstream processing into finished beer and their release through shelf-life. Three different commercial brands of lager beer were freeze-dried and reconstituted (30% w/w in pure water), providing a concentrated solution of ‘beer matrix’. The affinity of each matrix towards selected aldehydes was investigated. Results indicated that the beer brands showed considerable differences in terms of their binding of and interactions with aldehydes. Challenge experiments, where additional aldehydes were added, indicated that 3-methylbutanal was relatively effective at displacing other bound aldehydes, whereas, for example, hexanal was not. The competitive nature of binding, the complexity of the interactions and the need for further studies in this area were all confirmed. This research confirmed that multiple analytical indicators of flavour stability are required to build a full picture of beer staling potential, due to the complexity of the product and the relevant chemical pathways. Whilst indicators measured in the brewhouse did not correlate with values in fresh green beer – due to the ‘levelling’ impact of yeast – differences in flavour stability through shelf-life emerged which could be related to upstream indicators of, for example, thermal load and staling aldehyde levels. Effects with adjunct usage rate were non-linear at the highest adjunct rates, due to the requirement to amend mash conditions to balance wort FAN. In general, use of unmalted adjuncts was positive for flavour stability, but further studies of FAN-balancing techniques (mash schedule adjustment/ exogenous protease addition /wort supplementation) are required to identify optimal strategies at high levels of adjunct usage (40% or above).